1987
DOI: 10.3109/00498258709167407
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the metabolic fate of valproic acid in the rat using stable isotope techniques

Abstract: 1. The metabolic fate of two specifically deuterated analogues of valproic acid (VPA), [2-2H1]VPA and [3,3-2H2]VPA, was studied in the rat following i.p. injection. 2. A total of 11 urinary metabolites of each labelled substrate were detected by g.l.c.-mass spectrometry. Those metabolites which resulted from oxidation of the drug at C-4 and/or C-5 retained the deuterium label(s), whereas products of oxidation at C-2 and/or C-3 exhibited varying degrees of deuterium loss. 3. The deuterium content of 3-hydroxy-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Two‐en is formed by mitochondrial β‐oxidation of valproate. It has been shown that 3‐en is reversibly formed by isomerization of 2‐en (Rettenmeier et al 1987). Both 2‐en and 3‐en are relatively major metabolites in human serum, which probably reflect β‐oxidative metabolism of valproate in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Two‐en is formed by mitochondrial β‐oxidation of valproate. It has been shown that 3‐en is reversibly formed by isomerization of 2‐en (Rettenmeier et al 1987). Both 2‐en and 3‐en are relatively major metabolites in human serum, which probably reflect β‐oxidative metabolism of valproate in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…The three products represented three VPA b-oxidation intermediates. Further studies on VPA metabolites formed in vivo (Jakobs and Lö scher 1978;Lö scher et al 1981;Nau and Lö scher 1982;Nau et al 1981Nau et al , 1984Rettenmeier et al 1987) reinforced the idea that b-oxidation is a major oxidative pathway of VPA metabolism.…”
Section: Mitochondrial B-oxidationmentioning
confidence: 94%
“…1989 olite is generally believed to arise as an intermediate in the possible P-oxidation of VPA. Recent evidence indicates that this metabolite is formed by P,,,-dependent a,-oxidation (Prickett and Baillie, 1984) in addition to apparent @-oxidation (Rettenmeier et al, 1987), which seriously limits reliance o n this metabolite as a n indication of VPA (3oxidation. The observed absence of an effect on this metabolite further appears to disqualify it in this regard.…”
Section: Discussionmentioning
confidence: 99%